The Use of Intelligence in Indonesian Counter-Terrorism Policing - Paripurna, Amira (My University, 2017)
The world over, one of the most pressing issues confronting law enforcement agencies today concerns responding to and preventing terrorism. In general, counter-terrorism (CT) efforts fall into two categories: pre-crime and post-crime. Unlike post-crime efforts that respond to terrorist acts that have already occurred, pre-crime CT is generally understood to be “proactive,” where intelligence plays a key role in preventing events and acts of terrorism. Proactive CT necessitates strong cooperation between counter-terrorism actors and among the relevant agencies to share the intelligence they collect. In fact, intelligence sharing is fundamental to counter-terrorism cooperation. In places like the U.S. and the U.K., one of the most effective and influential manifestations of proactive CT has been an approach called Intelligence-Led Policing (ILP). ILP is currently considered to be a “promising” model of policing, a model that may positively contribute to prevention and reduction of serious crime, including terrorism, organized crime, and trans-organized crime. The core framework of ILP is proactive in nature: it offers a collaborative approach to law enforcement based on information sharing and police accountability, and enhanced by intelligence operations. This dissertation has sought to examine how and whether this ILP model is influencing the way the Indonesia is currently responding to terrorism. With this objective, it assesses and explores the ways that the Indonesian police and other counter-terrorism agencies collaborate and share information, using an ILP lens to analyze their strategic, tactical, and operational procedures and mechanisms. To drive effort, this dissertation addresses three main research questions: (1) What formal changes has Indonesia introduced into its policing structures post-Suharto and post-Bali Bombings? (2) Does the restructuring that Indonesia has undertaken represent an adoption of ILP as a primary strategy? (3) Do the Indonesian police and intelligence agencies collaborate and share information to prevent terrorism—and if they do, how? This qualitative study involved a thorough review of the extant literature, as well as analysis of in-depth interviews with key informants at counter-terrorism and security intelligence agencies. They consist on police special unit on counter-terrorism (Detasemen Khusus 88, Densus 88), national intelligence agency (Badan Intelijen Negara, BIN), and military strategic intelligence (Badan Intelijen Stratejik, BAIS), national coordinator of counter-terrorism (Badan Nasional Penanggulangan Terorisme, BNPT) and Indonesian financial intelligence unit (Pusat Pelaporan dan Analisis Transaksi Keuangan, PPATK). For additional background and context, interviews with academic scholars, members of parliaments, former jihadists and human rights activists were conducted. Through this analysis, the dissertation found that in Indonesia, current counter-terrorism policing relies primarily on intelligence to target, prioritize, and focus intervention. In this way, it reflects characteristics of an ILP strategy; in particular, it seems to reflect ILP most in how the agencies enhance law enforcement intelligence. However, while law enforcement intelligence has successfully driven police actions on counter-terrorism, police are operating under a fragmented intelligence structure. Collaboration and information-intelligence sharing happen in limited ways, generally on only a strategic level. At the same time, operational and tactical approaches have been shared only in informal ways. This study concluded that law enforcement intelligence has formed the backbone of CT policing in Indonesia; however, a number of essential elements from the ILP framework are missing from Indonesia’s efforts. Among other things, Indonesia is missing an integrated intelligence structure, especially formal policies and guidelines, mechanisms for sharing information within and among agencies. The result of this study provides an important first step in understanding the current implementation of CT policing in Indonesia—particularly, the pre-event aspect of CT. It also contributes to a better understanding of how information sharing could be improved among law enforcement and security intelligence agencies for improving terrorism prevention measures in Indonesia. Ultimately, this study recommends that the government provide guidance and promulgate regulations establishing coordination mechanisms to support the appropriate, effective, and timely sharing of both intelligence and sensitive information for law enforcement. In addition, it recommends the adoption of legislation to clarify how intelligence may be used in criminal proceedings, enabling a balance between the importance of intelligence products and protections for a fair trial. Safeguards will be needed to keep the democratization process on the right track while promoting security and public order.
Thesis (Ph.D.)--University of Washington, 2017-06
Keywords: Counter-Terrorism; Crime; Criminal Justice; Information Sharing; Intelligence; Policing; Law; Criminology; Political science; Law